2016
DOI: 10.5301/jva.5000535
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Peritoneal Dialysis or Hemodialysis Catheter Dialysis

Charmaine E. Lok

Abstract: Worldwide, there is a steady incident rate of patients with end-stage kidney disease (ESKD) who require renal replacement therapy. Of these patients, approximately one-third have an "unplanned" or "urgent" start to dialysis. This can be a very challenging situation where patients have either not had adequate time for education and decision making regarding dialysis modality and appropriate dialysis access, or a decision was made and plans were altered due to unforeseen circumstances. Despite such unplanned sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…Also, despite careful CKD care follow-up, patients encounter intercurrent events that lead to dialysis initiation. This is evidenced by the approximately 20%-40% of patients who initiate dialysis urgently (12,70) and are unlikely to have an established and useable vascular access. On the contrary, some patients do not progress to start dialysis.…”
Section: Process Factorsmentioning
confidence: 99%
“…Also, despite careful CKD care follow-up, patients encounter intercurrent events that lead to dialysis initiation. This is evidenced by the approximately 20%-40% of patients who initiate dialysis urgently (12,70) and are unlikely to have an established and useable vascular access. On the contrary, some patients do not progress to start dialysis.…”
Section: Process Factorsmentioning
confidence: 99%
“…16,17 In a recently published paper, Lok et al reported that about a third of the patients worldwide have unplanned RRT starts, an event that makes the discussions around the development of diagnosis and treatment, including the choice of mode of dialysis and the implantation of a dialysis access, more challenging to the health care team. 18 PD has been seen as a viable and safe alternative to HD in unplanned dialysis starts in developed and developing nations, nurturing the growth of PD programs. 19,20,21,22,23 Casaretto et al 24 and Ghaffari et al 25 reported that urgent-start PD programs call for novel infrastructure and specific care processes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of lack of timely access to PD catheter insertions for acute dialysis starts by surgery or radiology in our institution, our nephrology division supported a bedside PD catheter program initiated by a sole staff nephrologist. Preliminary results (n553) from our center have shown a success rate of 93% (7% primary failure rate), with 100% used for dialysis (18). Long-term committed use of PD after insertion by nephrologists compared with surgeons or radiologists has been reported in a study of .3000 patients on PD (26).…”
Section: Discussion Of Question 1bmentioning
confidence: 99%
“…Typically, urgent start PD is performed with low-fill volumes with the patient in the supine position with a cycler to reduce intra-abdominal pressure and avoid pericatheter or incisional leaks. It is an excellent HD CVC sparing strategy with the additional benefits of PD (18). However, proper training and logistic support is required throughout all phases of its implementation.…”
Section: Discussion Of Question 1bmentioning
confidence: 99%